Methadone dosing and prescribed medication use in a prospective cohort of opioid‐dependent pregnant women. (11th February 2013) - Cleary, Brian J.; Reynolds, Kieran; Eogan, Maeve; O'Connell, Michael P.; Fahey, Tom; Gallagher, Paul J.; Clarke, Tom; White, Martin J.; McDermott, Christine; O'Sullivan, Anne; Carmody, Deirdre; Gleeson, Justin; et al.
Abstract Aims This study aimed to (i) describe methadone dosing before, during and after pregnancy, (ii) to compare the incidence of neonatal abstinence syndrome (NAS) between those with dose decreases and those with steady or increasing doses and (iii) to describe prescribed medication use among opioid‐dependent pregnant women. Design Prospective cohort study. Setting Two Irish tertiary care maternity hospitals. Participants A total of 117 pregnant women on methadone maintenance treatment (MMT) recruited between July 2009 and July 2010. Measurements Electronic dispensing records from addiction clinics and the Primary Care Reimbursement Service were used to determine methadone doses and dispensed medications in the year preceding and the month following delivery. The Finnegan score was used to determine need for medical treatment of NAS. Findings Of the 117 participants, sufficient dosing data were available for 89 women treated with MMT throughout pregnancy; 36 (40.4%) had their dose decreased from a mean pre‐pregnancy dose of 73.3 mg [standard deviation (SD) 25.5] to a third‐trimester dose of 58.0 mg (SD 26.0). The corresponding figures for those with increased doses (n = 31, 34.8%) were 70.7 mg (SD 25.3) and 89.7 mg (SD 21.0), respectively. The incidence of medically treated NAS did not differ between dosage groups. Antidepressants were dispensed for 29 women (25.7%) during pregnancy, with the rate decreasing from pre‐pregnancy to postpartum. Benzodiazepines were prescribed for 43 women (38.0%). Conclusion In the Irish health service, opioid‐dependent women frequently have their methadone dose decreased during pregnancy but this does not appear to affect the incidence of the neonatal abstinence syndrome in their babies.